Dwi Monika Ningrum THE ROLE OF A PHARMACIST IN APPLYING THE STANDARD OF PHARMACEUTICAL CARE IN PHARMACY AT WEST LOMBOK - Dwi Monika Ningrum (Politeknik Medica Farma Husada Mataram, 2021)
Pharmaceutical care is a direct and responsible service to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life. The standards of Pharmaceutical care in pharmacies are designed to serve as guidelines for pharmacist practice in carrying out the profession, to protect the public from unprofessional services and to protect the profession in carrying out pharmaceutical practices. This study aims to describe the implementation of pharmaceutical service standards in pharmacies in West Lombok Regency. This research is a non-experimental qualitative descriptive research with cross sectional data collection with a total of 40 pharmacies in Lombok Barat. The collection data was carried out using questionnaire sheets to respondents who were willing. The results obtained in this study include the management standards of pharmaceutical supplies by pharmacists together with pharmacist assistant with a percentage of 35.4%, clinical pharmacy service standards carried out by pharmacists with a percentage of 38%, and quality evaluation implementation. service in the pharmacy is carried out by pharmacists by 80%. The conclusion obtained in this study is that the role of pharmacists is very influential on the success of services, especially in clinical pharmacy services, namely in drug information services, monitoring drug therapy, and monitoring drug side effects which really require the role of a pharmacist.